Lithium–Sulfur Batteries: Hierarchical Defective Fe3‐xC@C Hollow Microsphere Enables Fast and Long‐Lasting Lithium–Sulfur Batteries (Adv. Funct. Mater. 22/2020). (25th May 2020) - Zhang, Yongguang; Li, Gaoran; Wang, Jiayi; Cui, Guoliang; Wei, Xiaoling; Shui, Lingling; Kempa, Krzysztof; Zhou, Guofu; Wang, Xin; Chen, Zhongwei
Abstract : In article number 2001165, Xin Wang, Zhongwei Chen, and co‐workers develop a hierarchical Fe3− x C@C hollow microsphere consisting of Fe‐deficient Fe3− x C subunits with a mesoporous carbon coating that serves as an excellent lithium polysulfide adsorbent to immobilize the sulfur species against their shuttling behaviors, as well as an efficient catalyst to promote the sulfur conversion reaction kinetics. The cation‐deficient design holds great promise in the development of high‐performance Li‐S batteries.